2022
DOI: 10.1007/s12369-022-00878-x
|View full text |Cite
|
Sign up to set email alerts
|

Power-Posing Robots: The Influence of a Humanoid Robot’s Posture and Size on its Perceived Dominance, Competence, Eeriness, and Threat

Abstract: When interacting with sophisticated digital technologies, people often fall back on the same interaction scripts they apply to the communication with other humans—especially if the technology in question provides strong anthropomorphic cues (e.g., a human-like embodiment). Accordingly, research indicates that observers tend to interpret the body language of social robots in the same way as they would with another human being. Backed by initial evidence, we assumed that a humanoid robot will be considered as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…One pertained to human factors, such as self-efficacy in operating machines (Latikka et al, 2019) and user personality traits, with extraversion being linked to favorable attitudes and neuroticism to unfavorable ones (Damholdt et al, 2015). The other direction pertained to technological features, including robots’ appearance (Mori, 1970), postures (Stein et al, 2022), and perceived mind (attributing to robots mental status such as the capacity to feel; Dang & Liu, 2021). In our research, we emphasized sociality.…”
Section: Discussionmentioning
confidence: 99%
“…One pertained to human factors, such as self-efficacy in operating machines (Latikka et al, 2019) and user personality traits, with extraversion being linked to favorable attitudes and neuroticism to unfavorable ones (Damholdt et al, 2015). The other direction pertained to technological features, including robots’ appearance (Mori, 1970), postures (Stein et al, 2022), and perceived mind (attributing to robots mental status such as the capacity to feel; Dang & Liu, 2021). In our research, we emphasized sociality.…”
Section: Discussionmentioning
confidence: 99%
“…6A and 6B), a much heavier package would likely affect the experiment outcome. Third, we did not employ various AMR parameters, such as size and appearance [22,37,79], acceleration [76], sound [67], and moving and approaching directions [38,80]. Rubagotti et al noted that these factors have been extensively shown to affect perceived safety and comfort [27].…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of the sequential decision‐making ability of reinforcement learning, healthcare applications such as dynamic treatment regimens and Just‐in‐Time‐Adaptive‐Interventions (JITAIs) can be further enhanced. However, there have been recent incidents of deploying physical robots causing threats to humans (Stein et al, 2022). It is recommended to build virtual robots using reinforcement learning agents to monitor patients and predict unprecedented events.…”
Section: Future Direction Of Ai On Rpmmentioning
confidence: 99%